2020 IEEE Conference on Games (CoG) 2020
DOI: 10.1109/cog47356.2020.9231892
|View full text |Cite
|
Sign up to set email alerts
|

Motion-Based Educational Games: Using Multi-Modal Data to Predict Player’s Performance

Abstract: Multi-Modal Data (MMD) can help educational games researchers understand the synergistic relationship between player's movement and their learning experiences, and consequently uncover insights that may lead to improved design of movement-based game technologies for learning. Predicting player performance fosters opportunities to cultivate heightened educational experiences and outcomes. However, predicting player's performance utilising player-generated MMD during their interactions with educational Motion-Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
(65 reference statements)
2
11
0
Order By: Relevance
“…In numerous studies, predictive performance models containing fused data sources have outperformed predictive performance of the individual data sources (Cukurova et al, 2019 ; Giannakos et al, 2019 ; Liu et al, 2019 ; Sharma et al, 2019b , 2020c ; Lee-Cultura et al, 2020a ). For example, one study which used a modified-Pacman game, found that the fusion of EEG, eye-tracking and facial data streams, outperformed the individual data streams when predicting player performance (Giannakos et al, 2019 ).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In numerous studies, predictive performance models containing fused data sources have outperformed predictive performance of the individual data sources (Cukurova et al, 2019 ; Giannakos et al, 2019 ; Liu et al, 2019 ; Sharma et al, 2019b , 2020c ; Lee-Cultura et al, 2020a ). For example, one study which used a modified-Pacman game, found that the fusion of EEG, eye-tracking and facial data streams, outperformed the individual data streams when predicting player performance (Giannakos et al, 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, in an adaptive self-assessment test, the combination of eye-tracking, facial features, EDA, and HRV data showed lower error rates than the individual components when predicting engagement and performance (Sharma et al, 2019b ). In the same vein, combining features from eye-tracking, motion, EDA and HRV have resulted in better performance prediction during children's play with MBEG, than the individual data stream (Lee-Cultura et al, 2020a ). Lastly, in a diverse set of studies (e.g., games and learning tasks), the combination of facial data, EDA, BVP, and HRV resulted in a lower error rate while predicting participant's cognitive performance when compared against the error rate achieved by the individual features (Sharma et al, 2020c ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Player experience (challenge, frustration, and fun) can be modelled through controllable features of level design [21,22]. Instead of having users report their personality or emotions explicitly during the game play, it is interesting to do this unsupervisedly and implicitly [4], or through gaze, and physiological data [19]. Sequential models of in-game player behaviours are an alternative to aggregated players' actions, for predicting personality and expertise [6], assistance in serious games [36], churn prediction [17,38], or player categorisation from past and predicted behaviours [8].…”
Section: Related Workmentioning
confidence: 99%
“…Such data collections empower us to transcend the limits of human observation, by accessing real-time information on children's seemingly "invisible" cognitive, affective and physiological states [92]. Accordingly, sensing technologies are gaining traction as useful, reliable means of investigative practice for understanding multi-faceted problem solving phenomena and supporting learning in-situ [11,19], specifically in the domain of children's problem solving behaviours during interactive learning experiences [33,51,52,71]. Additionally, sensing technologies and their respective MMD, allow us to closely monitor and understand children's play and problem solving behaviours, leveraging the key affordances of MMD (e.g., temporality and direct access to indicators of children's cognitive and affective processes [19]).…”
Section: Introductionmentioning
confidence: 99%